Almost n-ary Subsemigroups and Fuzzy Almost n-ary Subsemigroups of n-ary Semigroups (European Journal of Pure and Applied Mathematics, 2025)
An n-ary semigroup is a non-empty set with an associative n-ary operation. Semi-groups and ternary semigroups are special cases of n-ary semigroups where n = 2 and n = 3,respectively. In this study, we introduce and explore the notions of almost n-ary subsemigroups and their fuzzy counterparts, termed fuzzy almost n-ary subsemigroups, within the framework of n-ary semigroups. Moreover, we demonstrate certain relationships between almost n-ary subsemigroups and fuzzy almost n-ary subsemigroups.